A study on returned medicine in Inpatients Pharmacy at Hospital Tuanku Fauziah - Hairuddin, Adibah; Bustamam, Nurul Izyan; Wan Mahamad, Wan Nur Bashirah (2009)
This study was carried out to identify and calculate the returned medicine from medical wards, determine the factors that lead to returned medicines, investigate the estimated cost of returned medicines from medical wards and suggest the appropriate solutions in reducing quantity of medication return. A random sample of returned medicines from medical wards was used in this study. The returned medicines were collected from four medical wards (4th Floor, 5th Floor, Ward 1 and Class 2 Medical) in Hospital Tuanku Fauziah based on inclusion and exclusion criteria over a period of two month (October- November 2008). A questionnaire was designed to evaluate reasons for returned medicines and these questionnaires were distributed to staff nurses from medical wards. A total of 16777 tablets/capsules were supplied to medical wards. From 16777 tablets/capsules, 9998 tablets/capsules were returned to inpatients pharmacy and 1950 tablets/capsules could not be reused. 5 Floor exhibited the main in medication supply (7512), medication return (4459) and non-reusable (811). In the meantime, cardiovascular drugs was the highest for medication supply (7274), returned (4478) and non-reusable (687) whereas genitor-urinary was the lowest rate for supply, returned and non-reusable medicines. The estimated total cost of the medications supply was RM3575.24. The cost of medication return was RM2053.80 and non-reusable cost was RM230.20. The main reason why drugs were returned was the change of therapy by physicians (86.25%) followed by 71.25% of the case was due to patients discharged. 63.75% responses stated change of drugs dose by physicians as one of the reasons. One the other hand, reason stated as ‘other’ was the lowest factor which contributed 21.25% responses. In conclusion, the study fortified the importance of analyzing return or unused medicines in order to establish method to diminish medication return and to reduce unnecessary health expenditure in our country. It also highlighted the inadequacies of the Perlis health system in the areas of prescription, dispensing and use of medicines.